Colorimetric detection of the potent carcinogen aflatoxin B1 based on the aggregation of L-lysine-functionalized gold nanoparticles in the presence of copper ions - Sánchez-Carrillo, Kaori; Quintanar-Guerrero, David; José-Yacamán, Miguel; Méndez-Albores, Abraham; Vázquez-Durán, Alma (Frontiers in Nutrition, 2024)
L-lysine functionalized gold nanoparticles (AuNPs-Lys) have been widely used for the detection of worldwide-interestworldwide interest analytes. In this work, a colorimetric assay for the detection of the carcinogen aflatoxin B1 (AFB1) based on the aggregation of AuNPs-Lys in the presence of copper ions was developed. For this purpose, AuNPs were synthesized in citrate aqueous solution, functionalized, and further characterized by UV-Vis, fluorescence, Fourier transform infrared spectroscopy (FTIR), nanoparticle tracking analysis (NTA), dynamic light scattering (DLS), and transmission electron microscopy (TEM). In general, the as-prepared AuNPS-Lys system (composed of 21.373×10 11 particles) offered a clear colorimetric response in the presence of AFB1 and Cu 2+ ions showing linearity in the range of 6.25 to 200 ng AFB1/mL, with a detection limit of 4.18 ng AFB1/mL via photometric inspection. Moreover, the performance of the proposed methodology was tested by means ofusing the 991.31 AOAC official procedure based on monoclonal antibodies in maize samples artificially contaminated with AFB1. There was a good agreement between the measured AFB1 concentrations in both assays, the average recoveries for the colorimetric and immunoaffinity assays were between 91.2-98.4% and 96.0-99.2%, respectively. These results clearly indicated that the colorimetric assay could be used as a rapid, eco-friendly, and cost-effective platform for the quantification of AFB1 in maizecereal-based products.